Genetic genealogy of Y-chromosome in the Zhetiru tribe of the Kazakh population from Kazakhstan - Zhunussova, Aigul; Tayshanova, Saltanat; Bukayev, Alizhan; Bukayeva, Ayagoz; Aidarov, Baglan; Temirgaliev, Radik; Sabitov, Zhaxylyk; Zhabagin, Maxat (Frontiers in Genetics, 2025)
IntroductionThe Y chromosome, transmitted exclusively through the paternal line, is a well-established tool for verifying genealogical data. The Kazakh tribe Zhetiru in Kazakhstan, comprising seven clans, has conflicting historical and genealogical narratives regarding its origin—either as a union of seven independent clans or as descendants of a single common ancestor. A detailed genetic investigation has not yet addressed this question.Methods350 male volunteers from the Zhetiru tribe were analyzed using 23 Y-STR loci and 17 Y-SNPs. We calculated genetic distances using Arlequin and STRAF, and explored genetic structure with median-joining networks using a comparative dataset of over 3,000 Kazakh individuals.ResultsAt the tribal level, haplotype diversity (0.997) and haplogroup diversity (0.91) are high. However, at the clan level, haplotypic diversity decreases, revealing clear founder effects in the main haplogroups of Kerderi (R1a1a), Kereit (N1a2), Tama (C2a1a3), and Teleu (J2a2). The genetic structures of Zhagalbaily, Ramadan, and Tabyn indicate additional sub-clan founders. The ages of key clusters suggest stable genetic lineages for over 1,000 years. Zhetiru clans do not form a distinct genetic cluster among Kazakh tribes but demonstrate genetic affinities with others.ConclusionThis study demonstrates the effective application of genetic genealogy approaches in verifying historical and genealogical records concerning the Zhetiru tribe and determining its origin from distinct, genetically independent clans.